2020
DOI: 10.1002/elps.201900395
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of antigen‐containing nanoparticles using microfluidics with Tesla structure

Abstract: The polyethyleneimine (PEI)-based antigen delivery system has been proved valuable for therapeutic vaccines. However, the previous bulk mixing method is not ideal to prepare PEI-base antigen-containing nanoparticles. The wide-size distribution and poor reproducibility limit its further application. In this research, we developed a microfluidic method to prepare nanopolyplexes on chips with Tesla structure to improve the fabrication. The structure and bioactivity of protein were not hampered by the shearing for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…The structure was illustrated in Figure 1 A,B, clearly showing the microscopic size and shape characteristic. siRNA lyophilized powder was diluted with diethylpyrocarbonate (DEPC)-treated ddH 2 O to 2 μM and the solution was injected from one inlet, while CEL was dissolved with DEPC-treated ddH 2 O to different concentrations according to N/P ratio and injected from another inlet using syringe pumps (Langer, LSP01-2A and LSP02-1B, Hebei, China), similar to our previous study [ 46 ]. Initially, the single factor experiment was designed to optimize two important parameters, FRR and TFR.…”
Section: Methodsmentioning
confidence: 99%
“…The structure was illustrated in Figure 1 A,B, clearly showing the microscopic size and shape characteristic. siRNA lyophilized powder was diluted with diethylpyrocarbonate (DEPC)-treated ddH 2 O to 2 μM and the solution was injected from one inlet, while CEL was dissolved with DEPC-treated ddH 2 O to different concentrations according to N/P ratio and injected from another inlet using syringe pumps (Langer, LSP01-2A and LSP02-1B, Hebei, China), similar to our previous study [ 46 ]. Initially, the single factor experiment was designed to optimize two important parameters, FRR and TFR.…”
Section: Methodsmentioning
confidence: 99%
“…This design significantly enhanced the mixing in the gear-shaped channel, leading to more homogeneous silica NPs populations with reduced energy consumption. Additionally, a tesla-micromixer was used to produce antigen-coated NPs (Figure B.2) . This peculiar structure effectively enhanced the mixing of fluids by inducing transversal convection, leading to NPs with smaller sizes, higher monodispersity, and reproducibility.…”
Section: Microfluidic Devicesmentioning
confidence: 99%
“…Additionally, a tesla-micromixer was used to produce antigen-coated NPs (Figure 4B.2). 101 This peculiar structure effectively enhanced the mixing of fluids by inducing transversal convection, leading to NPs with smaller sizes, higher monodispersity, and reproducibility. Tesla's micromixer efficiency usually relies on the asymmetric structure of the channel or the flow rate ratio of the fluids.…”
Section: Re Vlmentioning
confidence: 99%
“…For example, the use of a Tesla structure in microfluidic devices has been shown to benefit insulin encapsulation in PLGA NPs; primary parameters such as flow rate and the concentration of PLGA and insulin do not interfere with the physical characteristics of the produced NPs. 162 Whether these could be translated to general BD-loaded polymeric NP production with microfluidic devices still needs investigation. Overall, it is suggested that the combination of conventional synthesis methods with microfluidic devices can facilitate the use of polymers for BD encapsulation in the future.…”
Section: Insights For Future Directions Perspectives and Translation ...mentioning
confidence: 99%